FRI0148 Non-Adherence and Non-Persistence in the Therapy of Rheumatoid Arthritis with Methotrexate: An Analysis of German Claims Data Based on 9, 592 RA Patients. (9th June 2015) - Mueller, S.; Krüger, K.; Maywald, U.; Fuchs, A.; Flacke, J.-P.; Haug-Rost, I.; Heinisch, H.; Wilke, T.
Abstract : Background: According to current treatment guidelines Methotrexate (MTX) is the first-line choice of disease-modifying antirheumatic drug (DMARD) therapy of rheumatoid arthritis (RA). Previous studies indicated that non-persistence (NP)/non-adherence (NA) are widespread problems in the treatment of RA-patients. However, real world data addressing NP-/NA-problems are rare. Objectives: The purpose of this study was to describe the extent of NP/NA in RA-patients treated with MTX in Germany. Methods: Anonymous claims data from a German sickness fund (AOK PLUS) covering the years 2010-2013 were used. We included patients with at least one confirmed RA-diagnosis. However, all patients with an additional diagnosis of at least one of the following diseases were excluded: (e.g. axial spondyloarthritis, Bechterew's disease, psoriatic arthritis), NP was measured for patients who were newly treated with MTX orally/subcutaneously (no prescription of MTX in previous 12 months before index date); minimum observational period from first MTX-prescription onwards was 24 months. NP was defined as a medication gap of more than 12 weeks. Applied assumptions with regards to prescribed daily dosage (PDD) which was itself not available in the database were pre-tested in a validation study with 7 rheumatology practices which documented 935 prescriptions/their PDD for 160 RA-patients. Adherence was calculated using the medication possession ratio (MPR) between an observed first and last prescription (after confirmed RA-diagnosis); NA was defined as MPR<80%. The adherence was assessed since first until last prescription or, in case a patient became NP, until the first treatment gap >12 weeks was observed. Results: In total 62, 204 RA-patients could be identified. Of these, 9, 796 (15.7%) got at least one prescription of MTX after a RA-diagnosis. 204 patients with an intravenous application of MTX were also excluded. So, our analysis was based on 9, 592 RA patients (mean age 64.4 years, 72.7% female, average Charlson Comorbidity Index of 4.1). Of these, 1, 118 patients could be considered as newly treated (therapy start before end of 2011). Overall MTX-MPR from first prescription until end of the 24-months-observational period for these 1, 118 patients was 60.7%. Of these patients, 379 patients (33.9%) discontinued MTX therapy (NP) within 24 months. For these, mean time to discontinuation was 29.1 weeks (median: 30). The observed NP rate was higher for oral MTX than for subcutaneous MTX (36.5% versus 29.8%). Adherence was calculated for a total of 8, 345 patients. The average observed MPR was 90.4%; 19.4% of the patients could be classified as NA (23.1%/11.9% in patients with oral/subcutaneous application). Conclusions: More than 30% of the RA patients discontinue their MTX treatment early. Among patients still generally persisting with therapy, about 19% can be classified as NA. Approximately one third of newly treated patients and additional 19% of the persistent MTX-RA patients may be on NP/NA risk. So, this first analysis of a large German claims dataset showed that NA/NP is a considerable challenge in the real-world treatment of RA with MTX. Disclosure of Interest: S. Mueller Employee of: Institute for Pharmacoeconomics and Medication Logistics (IPAM), K. Krüger Consultant for: Roche, Speakers bureau: Roche, U. Maywald: None declared, A. Fuchs: None declared, J.-P. Flacke Employee of: Roche, I. Haug-Rost Employee of: Roche, H. Heinisch Employee of: Chugai, T. Wilke Consultant for: Roche, Novo Nordisk, GSK, BMS, LEO Pharma, Astra Zeneca, Bayer, Boehringer Ingelheim